An analytical model that links customer-perceived value and competitive strategies. Issue 4 (December 2018) - Echchakoui, Said
Abstract Several authors developed predictive analytic models that link the value that represents customers to a firm (i.e., customer lifetime value) to several outcome variables, such as customer profitability, in relationship marketing. However, similar models that link the value that customers perceive and firm outcomes or customer responses are uncommon. To reduce this gap, we construct an analytic model that links customer-perceived value and a company's competitive strategy, achieved through a multi-attribute model, analytic hierarchy processing, and a conceptualization of value that considers disparity between benefits and sacrifices. Operationalized in a context of industrial enterprise, the model predicts and orients a company's competitive strategy and extends generic competitive strategies introduced in Bowman's strategy clock mode by identifying when two strategies create competitive advantages.